2023
DOI: 10.1021/acsomega.2c08014
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Multitarget Activity of Wedelolactone against Alzheimer’s Disease: Insights from In Silico Study

Abstract: In this study, Wedelolactone's multitarget activity against Alzheimer's disease was examined using density functional theory and molecular docking techniques. At physiological pH, the pK a and molar fractions have been estimated. The most likely relative rate constants of two radical scavenger mechanisms are formal hydrogen transfer in a lipid environment and single-electron transfer in a water solvent. Compared to Trolox (k overall = 8.96 × 10 4 M −1 s −1 ), Wedelolactone (k overall = 4.26 × 10 9 M −1 s −1 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Both studies have demonstrated that such 4-hydroxycoumarins could be a leading class of novel multitarget-directed ligands for the potential treatment of AD. Du et al [ 154 ] have also attempted to elucidate the anti-AD potential of wedelolactone ( 109 ) by computational studies. Their results indicated that wedelolactone has exceptionally good affinity to both AChE and BChE, could scavenge hydroperoxyl radicals and act as a potent Cu(II) chelator.…”
Section: Coumarin Derivatives As Metal Chelatorsmentioning
confidence: 99%
“…Both studies have demonstrated that such 4-hydroxycoumarins could be a leading class of novel multitarget-directed ligands for the potential treatment of AD. Du et al [ 154 ] have also attempted to elucidate the anti-AD potential of wedelolactone ( 109 ) by computational studies. Their results indicated that wedelolactone has exceptionally good affinity to both AChE and BChE, could scavenge hydroperoxyl radicals and act as a potent Cu(II) chelator.…”
Section: Coumarin Derivatives As Metal Chelatorsmentioning
confidence: 99%